علاقة الفروقات الفردية بأداء فريق العمل - عزالدين بن قلية; الهادي وصيف تواتي; محمد بيه; عبد القادر دبار (university of eloued جامعة الوادي, 2024)
هدفت هذه الدراسة الى إبراز الدور الفعال للمورد البشري الذي يعتبر عامل أساسي في كل مؤسسة وهذا ما اداء الى اهتمام المؤسسة بالفروق الفردية وتحديد مستوياتهم من أجل تصنيفهم في طرق العمل بما يتوافق مع القدرات المهنية والعلمية والعملية للعامل، ولها دور في ابراز الفروق الفردية داخل فريق العمل في انجاز المهام بأقل تكلفة في وقت وجيز بكفاءة واتقان. ولتحيق ذلك تم استخدام إستبانة لجمع البيانات وزعت على عينة بلغ عددها 40عاملا في شركة المدروسة وتم استرجاع 30إستبانة تم استخدام الأدوات الإحصائية المناسبة للدراسة SPSS-v21 وتهتم هذه الدراسة بالتعرف على المفاهيم الأساسية للمتغيرين الفروق الفردية وبناء فريق العمل وكذلك التعرف على العلاقة بين المتغيرين وأثارهما على الشركة كما تدرس أداء فريق العمل وأنواعه حيث تم اعتمدنا على الدراسة التطبيقية في توضيح الفوارق وأداء فريق العمل داخل الشركة. This study aimed to highlight the effective role of human resources, which is considered a basic factor in every institution. This led to the institution's interest in individual differences and determining their levels in order to classify them in work methods in line with the professional, scientific and practical capabilities of the worker. It has a role in highlighting individual differences within the work team in completing tasks at the lowest cost in a short time with efficiency and mastery. To achieve this, a questionnaire was used to collect data and distributed to a sample of 40 workers in the studied company. 30 questionnaires were retrieved. The appropriate statistical tools for the study were used SPSS-v21. This study is concerned with identifying the basic concepts of the variables individual differences and building the work team, as well as identifying the relationship between the two variables and their effects on the company. It also studies the performance of the work team and its types, as we relied on the applied study to clarify the differences and performance of the work team within the company.
Keywords: الفروقات الفردية، فريق العمل، شركة بالنور individual differences; work team; Balnoor Company